Unveiling the dual threat: combined elevated triglyceride-glucose index and intracranial arterial stenosis burden for enhanced stroke risk stratification - Liao, Baoyi; Meng, Guilin; Liu, Xueyuan (Frontiers in Neurology, 2025)
BackgroundThe relationship between an elevated triglyceride-glucose index (TyG) combined with intracranial arterial stenosis (ICAS) and stroke recurrence remains incompletely understood. This study investigated how varying ICAS burdens influence the prognosis of ischemic stroke patients with different TyG levels.MethodsThis prospective cohort study analyzed a consecutively enrolled population of 712 acute ischemic stroke patients, with intracranial atherosclerotic burden quantitatively evaluated via computed tomography angiography (CTA) or three-dimensional time-of-flight magnetic resonance angiography (MRA), and stenosis severity graded according to WASID criteria. Participants were categorized into four mutually exclusive subgroups based on TyG index quartiles and ICAS status (presence/absence). To investigate exposure-response gradients, further stratification incorporated both ICAS severity (no/mild [<50%], moderate [50–69%], or severe [70–99% or occlusion] stenosis) and vascular involvement (single vs. multiple affected arterial territories). The primary endpoint was defined as ischemic stroke recurrence within a standardized 90-day follow-up period. Cox proportional hazards models examined adjusted associations between TyG/ICAS status and outcomes, complemented by Kaplan-Meier curves with log-rank tests for time-to-event visualization. Mechanistic pathways were delineated through causal mediation analysis employing Quasi-Bayesian approximation (100 Monte Carlo simulations) to quantify mediating effects between metabolic dysfunction and cerebrovascular outcomes.ConclusionThe synergistic combination of elevated TyG index and ICAS burden demonstrated superior prognostic value for 3-month stroke recurrence risk compared to either parameter independently, suggesting that concurrent assessment of insulin resistance (via TyG index) and vascular imaging biomarkers (via ICAS burden) may refine early risk stratification. This finding underscores the importance of integrating systemic metabolic dysfunction with structural cerebrovascular pathology to identify patients at heightened vulnerability during the critical post-stroke recovery window.